2009
DOI: 10.1073/pnas.0808778106
|View full text |Cite
|
Sign up to set email alerts
|

Consumers indirectly increase infection risk in grassland food webs

Abstract: Most pathogens exist within complicated food webs of interacting hosts, vectors, competitors, and predators. Although theory has demonstrated a variety of mechanisms by which predation and competition in food webs can indirectly control infection risk in hosts, there have until now been no experimental tests of this theory. We sampled the effect of long-term exclusion of large vertebrate herbivores on the prevalence of infection by a group of aphid-vectored viruses that infect grasses (barley and cereal yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 29 publications
3
82
1
Order By: Relevance
“…Loss of biodiversity might have extensive, positive or negative, impacts on disease transmission in natural ecosystems (Borer et al 2009, Haas et al 2011. Our study showed that tree diversity plays a role in biotrophic fungal pathogen infections of common European forestry species.…”
Section: Discussionmentioning
confidence: 94%
“…Loss of biodiversity might have extensive, positive or negative, impacts on disease transmission in natural ecosystems (Borer et al 2009, Haas et al 2011. Our study showed that tree diversity plays a role in biotrophic fungal pathogen infections of common European forestry species.…”
Section: Discussionmentioning
confidence: 94%
“…Our results demonstrate that alterations to the physical or biotic environment that cause non-random species losses and changes in the distribution of species traits can also alter infectious disease [34,55,64] dynamics. Thus, our results suggest that insights from ecological research can motivate further studies at the interface of disease ecology and statistical physics and mathematics in order to model interaction networks in complex host-pathogen systems and can provide general insights into the dynamics of infectious diseases in the face of increasing human impacts on global ecosystems [1,9].…”
Section: Host Ubiquity and Competence For Pathogen Spreadmentioning
confidence: 93%
“…Potential drivers of disease prevalence in both vectored and directly transmitted parasite systems include host abundance [22,34]; thus, the amplification or dilution of disease can be driven by the trajectory of host abundance with declining diversity. In this study, we found that the infection prevalence in our focal, vectored, generalist phytoviruses B/CYDVs increased with declining host diversity but was not explained by variation in abundance of the sentinel host B. hordeaceus.…”
Section: Host Species Diversity and Pathogen Prevalencementioning
confidence: 99%
“…Forbs (herbaceous flowering plants) are non-hosts, supporting neither aphids nor B/CYDV, but they compete with host grasses for soil and light. The final element is vertebrate herbivores, not within the transmission cycle in any way, but as selective grazers, removing forbs and stimulating plant regrowth, thereby increasing aphid colonization (Borer et al 2009). When these consumers were excluded from the system, B/CYDV infection prevalence decreased from 18% outside the exclosures to 5% inside, i.e.…”
Section: E V I D E N C E F O R D I L U T I N G O R a M P L I F Y I N mentioning
confidence: 99%